2007
DOI: 10.1149/1.2732074
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Synthesis of a PtRu∕Nb[sub 0.1]Ti[sub 0.9]O[sub 2] Electrocatalyst for Methanol Oxidation

Abstract: Niobium was doped into anatase TiO 2 support at 10 mol % ͑Nb 0.1 Ti 0.9 O 2 ͒ using sol-gel chemistry. A PtRu/Nb 0.1 Ti 0.9 O 2 catalyst was synthesized by LiBH 4 reduction in tetrahydrofuran. The methanol electro-oxidation activity of the catalyst shows that this oxide support was electrically conductive. The current ͑A/g Pt ͒ was 6% higher on the PtRu/Nb 0.1 Ti 0.9 O 2 catalyst compared to a commercial PtRu/C catalyst at 25°C. The electrochemically active surface area of the PtRu/C was 94% higher than PtRu/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 7 publications
0
71
0
Order By: Relevance
“…It is known that rutile (TiO 2 ) can be doped with other cations to prepare Ti 1−x M x O 2 , where M = Zr, Hf, V, Nb, Ta, Cr, Mo, W, Ru, Os, Ir and Sn, and some of these oxides have been evaluated in electrochemical environments (Chang 1968;Sakata et al 1969;Horkans & Shafer 1977;Pejryd 1986;Smith et al 1998;Murata et al 2000;Roy et al 2000;Chen et al 2003;Colomer & Velasco 2007;Garcia et al 2007;Sasaki et al 2008). In this paper, we discuss the preparation and properties of W-doped TiO 2 (rutile phase: Ti 1−x W x O 2 ) and explore the preparation and use of 50 nm nanoparticles suitable for catalyst supports.…”
Section: This Journal Is © 2010 the Royal Societymentioning
confidence: 99%
“…It is known that rutile (TiO 2 ) can be doped with other cations to prepare Ti 1−x M x O 2 , where M = Zr, Hf, V, Nb, Ta, Cr, Mo, W, Ru, Os, Ir and Sn, and some of these oxides have been evaluated in electrochemical environments (Chang 1968;Sakata et al 1969;Horkans & Shafer 1977;Pejryd 1986;Smith et al 1998;Murata et al 2000;Roy et al 2000;Chen et al 2003;Colomer & Velasco 2007;Garcia et al 2007;Sasaki et al 2008). In this paper, we discuss the preparation and properties of W-doped TiO 2 (rutile phase: Ti 1−x W x O 2 ) and explore the preparation and use of 50 nm nanoparticles suitable for catalyst supports.…”
Section: This Journal Is © 2010 the Royal Societymentioning
confidence: 99%
“…[2][3][4][5][6] 15,[18][19][20] To fundamentally solve this technological issue and improve electrocatalyst durability, alternative carbon-free electrocatalyst support materials such as tin oxide (SnO 2 ) 21-29 and titanium oxide (TiO x ) [30][31][32][33][34] have also been proposed. It has been shown that SnO 2 is a promising alternative platinum support, since it has good electronic conductivity and thermochemical stability under the strongly acidic cathode conditions in a PEFC.…”
mentioning
confidence: 99%
“…Some of these doped titania supports have been catalyzed and evaluated for electrochemical stability and activity in a PEFC. Most of the doped titania materials have electronic conductivities in the interval 0.1-1 S · cm −1 (substantially lower than carbon catalyst supports), but showed activities for the oxygen reduction reaction that were comparable to commercial Pt/C catalysts when evaluated in a rotating disk electrode (RDE) (25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Significancementioning
confidence: 99%